Speech by the Honourable Chief Minister Penang at the Penang Medical Practitioner Society Annual Dinner and Dance to be held at the Peking Restaurant Penang on Saturday 13th November 1976 at 8.00 p.m. - Lim, Chong Eu (1976)
I thank you for having so kindly invited my wife and I to your Annual Dinner tonight. It is indeed a great pleasure to be with you and I must say it right from outset that if it had not been for the fact that I have not speak the pleasure will be even greater.